Humala antes de Ollanta: evolución política del nuevo presidente peruano - Nesbet-Montecinos, Felipe (European Review of Latin American and Caribbean Studies, 2011)
Humala before Ollanta: political evolution of the new Peruvian presidentThe unexpected election of Ollanta Humala as the new president of Peru generated many question marks and burning feelings among the international community and Peruvians in general. Some of these mysterious reactions can be explained by observing the road that Humala took to arrive at the presidency. The present article seeks to examine the evolution of Humala’s political thought, going back to his family origins, which determined the better part of his political ideology; his passage through the Peruvian army; the characteristics of the etnocacerista or ethnic nationalistic movement, in which he launched himself politically; his attempted coup d’état of 2001; and ending with his presidential campaign of 2006, which he lost by a narrow margin. Resumen:La sorpresiva elección de Ollanta Humala como nuevo presidente del Perú, generó muchísimas interrogantes y resquemores entre la comunidad internacional y los propios peruanos. Algunas de estas incógnitas se pueden dilucidar observando el camino que llevo a Humala hasta la presidencia. El presente artículo busca revisar la evolución del pensamiento político de Humala, remontándose a su origen familiar, que determino buena parte de su ideario político; su paso por el ejército peruano; las características del movimiento etnocacerista, en el cual se inicio políticamente; su intento de golpe de Estado de 2001; y terminando con su campaña presidencial de 2006, que perdió por estrecho margen.